Menyimak Kandungan Damai Dalam Sentuhan Karya Shukri Zain - Wasono, Sunu (Urban: Jurnal Seni Urban, 2021)
The idea, creative process, and theme of a poet's poetry can be traced through in-depth reading and interpretation of a number of poems, especially those contained in an anthology. This paper will discuss the thematic and stylistic reviews of Shukri Zain's poems in the anthology Damai Dalam Touch. This study uses descriptive analysis method through reading and in-depth meaning to reveal data, circumstances, phenomena, and is not limited to data collection, but also includes interpretation analysis. Through the analysis carried out, it was found several tendencies of Shukri Zain's poetry in the anthology Damai Dalam Touch, first, thematically, Shukri Zain's poems generally raised themes related to faith and Islam. Second, Shukri Zain's poems tend to be straightforward, but far from bombastic and vulgar. Finally, because the issues raised in his poems are related to matters of faith and Islam, the tone that is built in a number of Shukri Zain's poems tends to advise—not to say patronizing—the reader.Ide, proses kreatif, dan tema puisi seorang penyair dapat ditelusuri melalui pembacaan dan penafsiran mendalam terhadap sejumlah sajak, khususnya yang termuat dalam sebuah antologi. Tulisan ini akan membahas tinjauan tematik dan stilistik sajak-sajak Shukri Zain dalam antologi Damai Dalam Sentuhan. Penelitian ini menggunakan metode analisis deskriptif lewat pembacaan dan pemaknaan mendalam untuk mengungkapkan data, keadaan, fenomena, dan tidak terbatas pada pengumpulan data saja, namun juga meliputi analisis interpretasi. Lewat analisis yang dilakukan, ditemukan beberapa kecenderungan puisi karya Shukri Zain dalam antologi Damai Dalam Sentuhan, pertama, secara tematik, sajak-sajak Shukri Zain umumnya mengangkat tema yang berkaitan dengan keimanan dan keislaman. Kedua, sajak-sajak Shukri Zain cenderung lugas, namun jauh dari nada bombas dan vulgar. Terakhir, karena isu yang diangkat dalam sajak-sajaknya terkait dengan soal keimanan dan keislaman, nada yang terbangun dalam sejumlah sajak Shukri Zain cenderung menasihati—untuk tidak mengatakan menggurui—pembaca.